2014
DOI: 10.1002/tox.22054
|View full text |Cite
|
Sign up to set email alerts
|

Subacute toxicity assessment of diflubenzuron, an insect growth regulator, in adult male rats

Abstract: Diflubenzuron (DFB), an insecticide and acaricide insect growth regulator, can be used in agriculture against insect predators and in public health programs, to control insects and vectors, mainly Aedes aegypti larvae. Due to the lack of toxicological assessments of this compound, the objective of the present study was to evaluate the toxicological effects of subacute exposure to the DFB insecticide in adult male rats. Adult male rats were exposed (gavage) to 0, 2, 4, or 8 mg/kg of DFB for 28 days. No clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
(37 reference statements)
1
19
0
4
Order By: Relevance
“…Cyromazine was fed to Luhmann hens at a level of 0.15 ppm for 3 weeks, and hepatic lipids was increased [33]. Adult male rats were exposed (gavage) to 0, 2, 4, or 8 mg/kg of diflubenzuron for 28 days, but no significant alterations were observed in the liver and kidney histology [34]. Chlorfluazuron exposure resulted in 53% inhibition of the cytochrome P450 (CYP1A1/2) activities in human hepatic microsomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cyromazine was fed to Luhmann hens at a level of 0.15 ppm for 3 weeks, and hepatic lipids was increased [33]. Adult male rats were exposed (gavage) to 0, 2, 4, or 8 mg/kg of diflubenzuron for 28 days, but no significant alterations were observed in the liver and kidney histology [34]. Chlorfluazuron exposure resulted in 53% inhibition of the cytochrome P450 (CYP1A1/2) activities in human hepatic microsomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, the developmental toxicity of pyriproxyfen in zebrafish demonstrated the adverse morphological defects including behavioral effects, craniofacial defects, severe mortality, and teratogenicity at larval stages (Truong et al 2016). In addition, the assessment of subacute toxicity due to diflubenzuron (an IGR) in adult male rats exhibited significant decrease in testis weight, daily sperm production, and number of sperms in treated rats (Barros et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established in the literature that the use of pesticides, insecticides, larvicides and/or growth inhibitors is directly linked to genetic/genomic instability, which can increase predisposition to cancer [ 8 , 49 55 ], in addition to altering reproductive performance and causing hormonal disorders and male infertility [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Barros et al [ 57 ], the aforementioned effects may be caused by diflubenzuron, which has been widely used in the recent epidemics and is efficient in combating mosquitoes/vectors but toxic. No information on pyriproxifen is available in the literature regarding its mutagenic and/or teratogenic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation